Beneficial Effects of Probiotic Treatment on Gut Microbiota in Very Low Birth Weight Infants - Yue-feng Li; Chuan-rui Zhu; Xue-lei Gong; Hui-ling Li; Li-kuan Xiong; Ke-jian Wang; Guo-Sheng Liu (Gastroenterology Research and Practice)
The very low birth weight (VLBW) infant is at great risk for marked dysbiosis of the gut microbiota. In the present study, a total of 36 VLBW infants were randomly divided into two groups, who were treated with combined probiotics and placebo, and 72 fecal specimens on days 14 and 28 of life were collected from them. Finally, 32 fecal specimens extracted from 16 preterm VLBW infants were qualified and analyzed using 16S rRNA gene sequencing. The primary outcome was to evaluate the change of gut microbiota in VLBW infants after combined probiotic supplement. The secondary outcome was to analyze the correlation gut microbial composition and levels of cytokines. We found that probiotic treatment, but not placebo, decreased the α-diversity of gut microbiota in VLBW infants. At the phylum level, probiotic treatment strongly increased the abundance of Firmicutes, whereas that of Proteobacteria was significantly reduced. At the family level, Streptococcaceae and Lactobacillaceae became prevalent after probiotic treatment, while the relative abundance of Enterobacteriaceae was reduced in the meantime. Most notably, significant correlations were observed between Lactobacillaceae abundance and serum cytokine levels. Further studies are required to shed more light on the characteristics of gut microbiota of VLBW neonates. And the modulation of microbiota should be considered to improve the survival rate of VLBW infants.